Clinical outcomes of frozen–thawed single blastocyst transfer derived from low-quality day 3 embryos: A retrospective cohort study - Zhao, Xinyan; Zhou, Qiongge; Guan, Yichun (Frontiers in Endocrinology, 2025)
PurposeOur aim was to explore the clinical outcomes of a single blastocyst frozen–thawed transfer (single blastocyst frozen–thawed transfer (singleton frozen embryo transfer, sFET) derived from low-quality day 3 (D3) embryos.MethodsThis retrospective cohort study was conducted at the Reproductive Health Center of the Third Affiliated Hospital of Zhengzhou University. All data on sFET were collected between March 2016 and September 2022. Blastocysts derived from good-quality and low-quality D3 embryos were designated as the good-quality group and the low-quality group, respectively. Patients were divided into three groups according to age: <35 group, 35–39 group, and ≥40 group. Based on whether preimplantation genetic testing (PGT) was performed or not, the blastocysts derived from low-quality embryos were divided into the PGT group and the non-PGT group, respectively.ResultsAfter adjusting for female age, male age, infertility duration, and other potential confounders, the difference in the clinical pregnancy rate and the live birth rate in the good quality and low-quality groups maintained statistical significance [adjusted odds ratio adjusted odds ratio (aOR) = 0.32 and 0.35, p < 0.001]. When adjusting for embryo quality, the clinical pregnancy rate and the live birth rate in the <35 and 35–39 groups were significantly higher than those in the ≥40 group (OR = 3.02 and 3.56, p < 0.001; OR = 1.89 and 1.84, p < 0.001). Embryo quality significantly affected the clinical pregnancy rate and the live birth rate (p < 0.001). The clinical pregnancy rate and the live birth rate in the PGT group were higher than those in the non-PGT group (40.0% vs. 29.3% and 40.0% vs. 22.0%, respectively).ConclusionD3 embryos with low score/low quality can still obtain a certain live birth rate after further culturing to blastocysts with PGT.